Analisis Permintaan Uang di Indonesia - Aimon, Hasdi (Jurnal Kajian Ekonomi, 2014)
This study was foscused on demand for money (narrow and broad money). The demand for money is a function of riel nation income, interest, inflation adn lag demand for money. data used are time series (1980-2009) and being analysed with "demand for money samudram approprite with economics theory, the demand for many M2 is only riel nation income with signification but not the other. this condition was estimated based on; (1) community of Indonesia has not bank minded yet, (2) community of Indosesia only a little intrest on demanding mony for speculation objective, and (3) the money crisis problem hasn't finished yet